Unlocking the environmental potential of biochar: production, applications, and limitations - Siddiqui, Sazada (Frontiers in Sustainable Food Systems, 2025)
Biochar is a solid, alkaline, and porous material characterized by a high specific surface area, low bulk density, and strong adsorption capacity, produced through the pyrolysis of biomass under limited oxygen conditions. Due to its favourable physicochemical properties, biochar has gained attention as a potential renewable resource for managing soil fertility and improving crop yield. Numerous studies have shown that biochar application improves the soil fertility, increases the dry matter content of various crops and enhances crop yields, particularly when used in combination with inorganic or organic fertilizers. Biochar has been widely recognized as a promising tool for addressing various environmental challenges, including soil degradation, carbon sequestration, and remediation of organic pollutants and heavy metals. It is important to recognize specific limitations linked with biochar utilization, such as its variable effects across different soil types and the high cost and scalability challenges associated with its production and application. These concerns must be carefully considered when integrating biochar into soil and agricultural management practices. This review examines the production methods, physiochemical properties, and the agronomic potential of biochar, with a particular focus on its role in enhancing soil fertility and crop productivity. In addition, it explores the environmental benefits, the feasibility of biochar production in developing countries, and the potential limitations associated with its application.